Analysis of Rainfall Duration in Dramaga–Bogor in relation to Drainage Infrastructure Planning - Chessaramadhanty, Shaffadina Putry; Sapei, Asep; Prasetia, Rakhmat (Jurnal Teknik Sipil dan Lingkungan, 2025)
Dramaga Subdistrict, Bogor Regency, is the only area in West Java with a Monsoon-1 zone of the Year-Round Rainfall (YRR) type with rainfall exceeding 150 mm/month. The combination of duration and high intensity is an important factor that affects peak discharge/flooding, which in turn determines the dimensions of drainage channels. This study aims to analyze the duration of rainfall in Dramaga - Bogor and other characteristics. The analysis was conducted based on data from the Automatic Agroclimate Weather Station (AAWS) for 2018-2024 at the Bogor Climatology Station. It was found that the duration of heavy and very heavy rainfall in Dramaga was mostly 2 hours.  In addition, the highest monthly rainfall in Dramaga occurred in November (419.63 mm/month), while the lowest was in June (107.36 mm/month). Most of the rainfall occurred between 13:00 and 18:00 WIB, with the peak rainfall between 16:00 and 19:00 WIB.